Unravelling the mechanisms regulating embryonic epicardial cell proliferation. - Marín-Sedeño, Ernesto; Díaz del Moral, Sandra; Sánchez-Mata, Alicia; Díaz-Martínez, Luis; Lescroart, Fabienne; Ruiz-Villalba, Adrián; Pérez-Pomares, José María (My University, 2023)
Epicardial development is a highly complex process that relies on the precise coordination of cell proliferation and differentiation. The epicardium originates from an extracardiac cluster of cells, the proepicardium, which initially migrates to the myocardium and then massively expands to form the epicardial epithelial layer. Finally, some epicardial epithelial cells transform into mesenchymal cells via Epithelial-to-Mesenchymal Transition (EMT), and progressively invade the myocardial walls. The regulatory signals that govern epicardial cell proliferation remain largely unknown. To unveil the molecular signals involved in controlling epicardial cell proliferation, we examined the proliferation status of epicardial cells at different embryonic stages, and performed an RNA-seq analysis to identify candidate signalling pathways operating within the proepicardium. Then, we conducted in vivo and in vitro research to carefully dissect epicardial proliferation. Our results show that both canonical and non-canonical Wnt signals are involved in the regulation of epicardial proliferation during embryonic development.
Keywords: Células - Proliferación; Células cardiacas; Corazón; Cell proliferation; Epicardium; Heart development; Wnt signalling pathway